1970
DOI: 10.3329/bjvm.v7i1.5068
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence of Infectious Bronchitis in Chicken in Bangladesh

Abstract: The investigation was conducted to detect infectious bronchitis (IB) virus-specific antibody in chicken from some selected areas of Bangladesh. The indirect enzyme linked immunosorbent assay (iELISA) was performed to estimate the infectious bronchitis virus specific antibody. In case of sera-samples collected from BRAC diagnostic laboratory, Gazipur, 100% sera samples were found to be positive to IBV; the highest antibody titres were recorded as 9867.29. The average antibody titre of samples from Anis Poultry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…The findings is strong agreement with the report of , who demonstrated overall 58.00% seroprevalence of IBV in Fayoumi, RIR and local chickens of government poultry farms of Bangladesh. The results are also supported by the findings of Das et al (2009), who reported that overall seroprevalence of IBV in Bangladesh is 79.38%, and they found highest mean titer were 9867.29. These results also agreed with the report of previous study conducted by Alam et al (2003) and Biswas (2004) who found seroprevalence of IBV 92.06% and 77.83% respectively.…”
Section: Discussionsupporting
confidence: 86%
“…The findings is strong agreement with the report of , who demonstrated overall 58.00% seroprevalence of IBV in Fayoumi, RIR and local chickens of government poultry farms of Bangladesh. The results are also supported by the findings of Das et al (2009), who reported that overall seroprevalence of IBV in Bangladesh is 79.38%, and they found highest mean titer were 9867.29. These results also agreed with the report of previous study conducted by Alam et al (2003) and Biswas (2004) who found seroprevalence of IBV 92.06% and 77.83% respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Massachusetts strains (such as M41) are mainly used as vaccines in the field in Pakistan but we cannot totally rule out the use of 4-91 vaccines due to the limited control of imported vaccines. Similarly, high prevalence of IBV in backyard poultry (74%) and commercial poultry of Bangladesh (57%) were reported [26]. Sumi et al [27] classified Indian IBV isolates based on phylogenetic analysis within the Mass genotype (India/LKW/56/IVRI/08, now called GI-1) and the 793/B genotype (or 4-91 genotype, India/NMK/72/IVRI/10, now called GI-13).…”
Section: Discussionmentioning
confidence: 99%
“…Another researcher Das et al . [21] finds that a total of 79.38% sera samples of chickens of selected four districts of Bangladesh were seropositive. Although they do not differentiate the seroprevalence of IBV between vaccinated and non-vaccinated chickens.…”
Section: Discussionmentioning
confidence: 99%